Evaluasi Manajemen Risiko pada Proyek Konstruksi Pembangunan Tembok Banjir Sungai Batang Merao Kota Sungai Penuh - Dita Veviana Verasari; Asep Supriatna (Universitas Batanghari Jambi, 2026)
Sungai Penuh City is situated within the Bukit Barisan mountain range and tropical rainforest area. A significant portion of the city falls within the Kerinci Seblat National Park, while the urban area accounts for less than half of the city’s total territory. The upstream section of the Batang Bungkal River, which flows through Sungai Penuh, has a very low rainfall absorption capacity. Consequently, rainwater flows directly into the surrounding watershed areas, which is a major contributing factor to flash floods. The flash flood disaster that occurred in Sungai Penuh in January 2024 had its most severe impact in the Hamparan Rawang District. The objective of this study is to obtain accurate information regarding the probability and impact of risks that may arise during project implementation, in order to provide appropriate recommendations, suggestions, and further control measures to minimize risk levels. The risk management framework adopted in this study is based on the Australia/New Zealand Standards (1999). This research employs a quantitative descriptive method, with data collected through interviews and questionnaires distributed to respondents. Risk evaluation and control are conducted using the four approaches outlined in AS/NZS 4360, namely: Risk avoidance,Reducing the likelihood of occurrence,Reducing the consequences of occurrence, and Risk transfer to other parties.From the 42 identified risk indicators, 11 were classified under the Extreme Risk category.